City networks, mobility and environment: the Preliminary of the Avellino PTCP - Gargiulo, Carmela (TeMA - Journal of Land Use, Mobility and Environment, 2010)
This paper suggests reading the contents of the Avellino Ptcp, a very innovating plan from several points of view, especially for joining the traditional vast area planning and the “strategic” logic. In particular, the paper describes the guiding ideas, contents and strategies of the plan, mainly targeted to encourage sustainable development of an area with a delayed development such as the irpinia province , through the safeguard and exploitation of natural and historical-cultural resources, the building of medium and small cities networks and mobility networks at different scales, from the urban one to the international one, and interventions on the mobility system. In 2004, more than five years ago, the Preliminary of the Coordination Territorial Plan of the Avellino Province was adopted by absolute majority (with only two abstentions), after a two-year work carried out by the provincial offices and the Dipartimento di Pianificazione e Scienza del Territorio of the University of Naples “Federico II”. This work that exceeds the meaning and value of a preliminary and joins two different techniques of plan (the traditional one and the strategic one) is based on three fundamental ideas, strictly interlaced, which represent the guiding criteria followed by the Avellino Province in governing transformations. Those ideas, therefore, represent the grounds on which the Preliminary has been built and are the specification grid of the strategies and targets of the plan. They are the base of the choices worked out for the territorial compatible development, and refer to the operating actions of territorial transformation that the Local agencies, appointed to this task, will have to carry out in the next future. The three key-ideas of the Preliminary, described in the following paragraphs, refer to the main resources systems of the Avellino Province, which have undergone a deep analytical-interpretative investigation giving start to the current planning process.